2021
DOI: 10.1101/2021.12.19.473358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor eIF4E-5 is required for spermiogenesis in Drosophila melanogaster

Abstract: Drosophila sperm development is characterized by extensive post-transcriptional regulation whereby thousands of transcripts are preserved for translation during later stages. A key step in translation initiation is the binding of eukaryotic initiation factor 4E (eIF4E) to the 5' mRNA cap. Drosophila has multiple paralogs of eIF4E, including four (eIF4E-3, -4, -5, and -7) that are highly expressed in the testis. Other than eIF4E-3, none of these has been characterized genetically. Here, using CRISPR/Cas9 mutage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Beyond their involvement in the canonical translation of cellular mRNAs, other biological functions have been demonstrated for eIFs. Animal and plant studies have shown that germ cell and embryonic fates are greatly affected by the eIF4 factor complexes unique to those cell types (Baker and Fuller, 2007; Callot and Gallois, 2014; Dinkova et al ., 2005; Friday and Keiper, 2015; Shao et al ., 2021). The use of genetics and biochemistry has also identified unique roles for eIF4E and eIF4G isoforms in reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their involvement in the canonical translation of cellular mRNAs, other biological functions have been demonstrated for eIFs. Animal and plant studies have shown that germ cell and embryonic fates are greatly affected by the eIF4 factor complexes unique to those cell types (Baker and Fuller, 2007; Callot and Gallois, 2014; Dinkova et al ., 2005; Friday and Keiper, 2015; Shao et al ., 2021). The use of genetics and biochemistry has also identified unique roles for eIF4E and eIF4G isoforms in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…The use of genetics and biochemistry has also identified unique roles for eIF4E and eIF4G isoforms in reproduction. Furthermore, eIF4Es in plants, flies and frogs have shown unique roles in sexual development, judging by the reproductive phenotypes resulting from their deficiencies (Callot and Gallois, 2014; Ghosh and Lasko, 2015; Mazier et al ., 2011; Patrick et al ., 2014; Shao et al ., 2021). Viruses could take advantage of these additional biological functions to control protein stability, regulate their replication and facilitate their intra‐ and intercellular movements.…”
Section: Introductionmentioning
confidence: 99%